(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The purpose of this article is to identify the relevance and ways of motivation in learning the English language. This research examined student motivation in the classroom, teachers’ role and feedback from the students for promoting motivation. As well as the paper indicates the importance of intrinsic motivation for second language learners.